Use of carbon dioxide in underground natural gas storage processes - Nagy Stanislaw (Acta Montanistica Slovaca, 2006)
The possibility of use of carbon dioxide in gas storage processes is presented. The model of mixing process between CO2 and methane in porous media is given. The process of injection of carbon dioxide into a lower part of storage near the water –gas contact is modeled. The example of changes in the mixing zone is presented and discussed.